Full‐Spectrum Mechanochromic Photonic Films with Large Interparticle Distance - Hwan‐Young Lee; Jun‐Gu Kang; Young‐Seok Kim; Shin‐Hyun Kim (Advanced Science)
Abstract Non‐close‐packed crystalline arrays of colloidal particles in an elastic matrix exhibit mechanochromism. However, small interparticle distances often limit the range of reversible color shifts and reduce reflectivity during a blueshift. A straightforward, reproducible strategy using matrix swelling to increase interparticle distance and improve mechanochromic performance is presented. Photonic composites are initially prepared with silica particle arrays embedded in an elastomer matrix at volume fractions of 0.35–0.5. To increase interparticle distance, the composites are immersed in an elastomer‐forming monomer, causing the matrix to swell, followed by photopolymerization, thereby producing liquid‐free composites. The degree of swelling is controllable up to 3.16, depending on monomer choice, matrix volume fraction, and crosslinking density. The process can be repeated to further increase swelling up to 10.36. This method can reduce the volume fraction of silica particles from 40% to 3.8%, while interparticle distance increases from 53 to 257 nm. The swollen photonic composites exhibit a full visible spectrum under compression, while minimizing reflectivity loss. This allows red‐colored photonic composites to be transformed into vivid multicolor patterns when compressed with stamps featuring spatial height variations.